Association of parent-child health parameters and lifestyle habits - the "epi-family health" longitudinal study protocol - Diego Giulliano Destro Christofaro; William Rodrigues Tebar; Claudiele Carla Marques da Silva; Bruna Thamyres Ciccotti Saraiva; Amanda Barbosa Santos; Ewerton Pegorelli Antunes; Enrique Gervazoni Ferreira Leite; Isabella Cristina Leoci; Victor Spiandor Beretta; Gerson Ferrari; Jorge Mota; Luiz Carlos Marques Vanderlei; et al. (BMC, 2024)
Abstract Background Lifestyle and habits, cardiovascular risk factors (CRF), bone and mental health, dietary habits, physical activity, among others are developed in childhood and adolescence. Family environment has shown to play an important role in these outcomes. However, whether the parent-child relationship lifestyle habits and health parameters can be influenced by physical activity patterns still unclear. The objective of this study will be to monitor and investigate the associations between lifestyle habits between parents and their children longitudinally, as well as verify whether in more active parents, the possible associations with lifestyle habits are different from those of parents considered less active. Methods The sample will consist of parents (father, mother, or both) and their children /adolescents. The participants will be recruited through public call by flyers spread across all the regions of the city and also through social media. The health parameters will include cardiovascular (cardiac autonomic modulation, blood pressure and resting heart rate), bone mineral density, anthropometric indices, handgrip strength, mental health (quality of life, anxiety and depression symptoms and stress), self-reported morbidities and musculoskeletal pain. Lifestyle habits will include physical activity levels, sedentary behavior, sleep parameters, eating patterns, smoking and alcohol consumption. Sociodemographic variables of age, sex, ethnicity and socioeconomic status will be considered as covariates. The follow-up visits of data collection will be scheduled after a period of 12 months from the baseline assessment during every twelve months. Discussion The family environment has great potential to determine lifestyle habits in children and adolescents. Based on the results presented in the present study, we hope that health promotion actions can be better designed in the family environment.